Static Game Models and Applications Based on Market Supervision and Compliance Management of P2P Platform. (26th October 2020) - Pang, Sulin; Yang, Junkun; Li, Rongzhou; Cao, Jun
Abstract : This article focuses on the two-party static game between market supervisory organization and peer-to-peer (P2P) lending platform. Considering 4 game modes with both "strong supervision" and "weak supervision" of market supervisory organization and "compliance management" and "noncompliance management" of P2P lending platform, the paper establishes a static game model between P2P lending platform and market supervisory organization and solves the market equilibrium solutions. Based on income, cost, disguised cost, and fine of P2P lending platform and income, cost, and reward of market supervisory organization, it discusses conditional strategies that P2P lending platform selects "compliance management" or "noncompliance management" and that market supervisory organization selects "strong supervision" or "weak supervision, " respectively. Furthermore, the relevant influencing factors are analyzed which come from 18 P2P lending platforms in Guangdong Province of China, and the conclusions were in good agreement with the actual market. The research has scientific guiding significance.